Visionary-Oriented Leadership as a Foundation for Building Innovation: A Case Study of the Semarang City Health Office - Santoso, R. Slamet; Hidayat, Andri Rahmat; Rapha, Albert Jehoshua (Universitas Padjadjaran, 2026)
Innovative leadership serves as a crucial strategy in advancing an innovative work culture; thus, leaders frequently deal with obstacles in establishing a sustainable innovative leadership model. This study aims to examine the role of visionary elements in shaping innovative leadership within public sector organizations, with a focus on the Semarang (city) Health Office, which has successfully developed an innovative work culture while consistently enhancing its innovation quality index. A descriptive qualitative approach was applied to identify best practices in leadership processes. The findings indicated that innovative creative leadership at the Semarang City Health Office is characterized by visionary traits, including clarity and strategic delivery of vision, leader enthusiasm in realizing the vision, goal setting that emphasizes cross-sector collaboration, and the articulation of mission as a concrete manifestation of the established vision. The study concluded that visionary aspects should be prioritized as the initial phase in developing innovative leadership in the public sector, emphasizing cross-sector collaboration and vision concretization as the foundation for strengthening an innovative work culture.